2020
DOI: 10.29322/ijsrp.10.11.2020.p10762
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter Pylori Among Clients Attending Private Medical Laboratory Diagnostic Center In Karsh, Abuja, Nigeria

Abstract: Helicobacter pylori infection is the most common chronic bacterial infection around the world. It is a major aetiological factor in chronic gastric carcinoma and gastric mucosal associated lymphoid tissue lymphoma. A study on the prevalence of Helicobacter pylori was carried out among 204 clients comprised 118 males and 86 females aged 11-50years between September,2019 to march,2020.Blood samples were collected from clients and analyzed to determine the presence of Helicobacter pylori using Global Device H.pyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…This could be due to behavioral differences, as single individuals may lack a sense of responsibility in ensuring healthy meals are consumed regularly. This finding is consistent with previous studies by Enitan et al [25] and Okezie et al [22], which also reported a higher prevalence of H. pylori among singles.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This could be due to behavioral differences, as single individuals may lack a sense of responsibility in ensuring healthy meals are consumed regularly. This finding is consistent with previous studies by Enitan et al [25] and Okezie et al [22], which also reported a higher prevalence of H. pylori among singles.…”
Section: Discussionsupporting
confidence: 93%
“…This may be because people in this age range are more involved in agriculture or vegetable industries. However, this rate is consistent with previous studies by Okezie et al [22] and Zawaya et al [21], where the highest rates of infection were found among individuals aged 31-40 years (27.9%) and 35-44 years (27.8%), respectively.…”
Section: Discussionsupporting
confidence: 93%